Optimized BaZrO3 nanorod density in YBa2Cu3O6+x matrix for high field applications - Aye Moe Moe; Rivasto Elmeri; Rijckaert Hannes; Palonen Heikki; Huhtinen Hannu; Van Driessche Isabel; Paturi Petriina (IOP Publishing Ltd, 2022)
To maximize the flux pinning in high-temperature superconductor (HTS) thin film applications, we have experimentally studied the effect of BaZrO3 (BZO) nanorod density within the YBa2Cu3O6+x (YBCO) lattice. Even though the BZO decreases the self-field critical current density Jc (0) and the absolute Jc (B) at high fields is observed being the highest for 4% BZO doped YBCO, the maximized pinning property is observed at the level of 10% of BZO, when the distance between the outer edge of the nanorods is in the order of the diameter of the nanorod. In general, as also theoretically calculated, the flux pinning is increased even above 10% of BZO, but the improvement is limited by disturbance of the nanorod growth, weakening the flux pinning and decreasing the absolute Jc drastically. The results evidently show that by maximizing the flux pinning using higher BZO doping concentration than earlier expected and taking care of the maximum self-field Jc(0), which is strongly dependent on the electron mean free path, would offer the keys to resolve the challenges in the future HTS power applications.